HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG GIZI SEIMBANG DENGAN KEJADIAN STUNTING PADA BALITA USIA 2-5 TAHUN - Darmini, Ni Wayan; Fitriana, Lala Budi; Vidayanti, Venny (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022, 2022)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition with a z-score (TB/U) less than -2 SD (Standard Deviation). The prevalence of stunting in Indonesia is still high, with value above 25%. Mother's knowledge about balanced nutrition is very important to reduce incidence of stunting in toddlers. The higher the mother's knowledge about balanced nutrition, the better the provision of nutrition or food substances to toddlers will be. The purpose of this study was to determine the relationship between the level of knowledge of mothers about balanced nutrition with incidence of stunting in toddlers aged 2-5 years at the Puskesmas. This research is quantitative research with cross-sectional design. The research subjects were mother and child. The sample in this study amounted to 77 toddlers. The sampling technique used was purposive sampling. The inclusion criteria in the study were respondents who were willing to participate in the study and be able to read and write. The instrument was questionnaire and height was measured using microtoise. Bivariate analysis using Chi-Square test. The results showed that the mother's level of knowledge was mostly good (50,6%) and the highest incidence of stunting was not stunting (67,5%), the p-value of the bivariate analysis was 0,000 (<0,05). The conclusion in this study is there is significant relationship between the mother's level of knowledge about balanced nutrition and the incidence of stunting in toddlers aged 2-5 years at the Puskesmas.